2020
DOI: 10.5395/rde.2020.45.e32
|View full text |Cite
|
Sign up to set email alerts
|

The polymerization efficiency of a bulk-fill composite based on matrix-modification technology

Abstract: Objectives To evaluate the polymerization efficiency of a matrix-modified bulk-fill composite, and compare it to a conventional composite which has a similar filler system. The degree of conversion (DC%) and monomer elution were measured over different storage periods. Additionally, fillers' content was examined. Materials and Methods Cylindrical specimens were prepared, in bulk and incrementally, from Filtek Bulk Fill (B) and Filtek Supreme XTE (S) composites using a T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…Among the modifications proposed by the manufacturer, different monomers were developed and incorporated into its composition, such as the high molecular weight aromatic dimethacrylate (AUDMA), capable of increasing the rigidity of the polymer chain formed. 28 On the one hand, a more rigid chain increases the resistance of the material, 29 which may also have contributed to the higher values of DTS. On the other hand, it decreases the number of reactive groups on the organic matrix and hinders their mobility during the polymerization reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Among the modifications proposed by the manufacturer, different monomers were developed and incorporated into its composition, such as the high molecular weight aromatic dimethacrylate (AUDMA), capable of increasing the rigidity of the polymer chain formed. 28 On the one hand, a more rigid chain increases the resistance of the material, 29 which may also have contributed to the higher values of DTS. On the other hand, it decreases the number of reactive groups on the organic matrix and hinders their mobility during the polymerization reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when the polymer sheets are stored in water, the water is absorbed by diffusion, allowing the water molecules to get between the polymer chains, which facilitates their movement. With increasing temperature, the mobility of the polymer molecules also increases, leading to changes in the material [20,[29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…viscous composite has higher filler content than flowable composite that makes it better in mechanical properties, wear resistance, higher hardness and lesser in polymerization shrinkage (7)(8)(9)(10) . In addition, viscous composite contains high molecular weight monomers that increases the conversion degree and decrease polymerization shrinkage (19,20) . It is found that mechanical properties of 60 °C preheated viscous composites are considerably better after curing (21) .…”
Section: Discussionmentioning
confidence: 99%